Is “Islamic Banking” Islamic? Analysis of Current Debate on Shari‘ah Legitimacy of Islamic Banking and Finance - Mansoori, Muhammad Tahir (Islamic Studies, 2011)
This paper studies the doctrine of Hiyal in classical Islamic law and its application in the modern Islamic finance. The paper argues that most of the hiyal used in modern Islamic finance belong to the category of makharij i.e. way out or cleaver answers to difficult problems. It also discusses the methodology of talfiq and its Shari‘ah position. According to the author, majority of the Islamic banking transactions are largely Shari‘ah compliant. They comply with the requirement of a valid contract as they are free from riba, gharar, maysir and other Shari‘ah prohibitions. There are, however, certain transactions which represent stratagems and thus, defeat and frustrate the objectives of Shari‘ah. Such transactions and practices should be avoided by the Islamic banks. On 28th August, 2008, a fatwa was issued by the Shari‘ah scholars at Dar al-Ifta, Jami‘ah al-‘Ulum al-Islamiyyah, Binnori Town, Karachi, which declared present Islamic banking un-Islamic. This was followed by a number of fatwas favouring and opposing Islamic banking. This paper aims to analyze the current debates on the Shari‘ah legitimacy of Islamic banking. It examines the objections raised on Islamic banking to see whether the current Islamic banking practices are inconsistent with Shari‘ah principals and ideals or they are Shari‘ah compliant.